2017
DOI: 10.2147/ppa.s150388
|View full text |Cite
|
Sign up to set email alerts
|

The impact of pharmaceutical interventions on the rational use of proton pump inhibitors in a Chinese hospital

Abstract: BackgroundThe prescriptions of proton pump inhibitors (PPIs) have raised concern due to both huge increase in medical expenditure and the possible long-term adverse events caused by them; therefore, an approach to taper off the irrational use of PPIs by patients is clinically warranted. The aim of this study was to evaluate the impact of pharmaceutical interventions on the rational use of PPIs.Patients and methodsA single-center, pre- to post-intervention study (pharmaceutical interventions group and control g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 17 publications
(15 reference statements)
1
15
0
Order By: Relevance
“…A number of studies were performed at specific non-ICU hospital departments, such as the internal medicine department 32 , general ward 33 , infectious disease ward 34 , or a pulmonary medicine ward 35 (Table 2 ). In other studies, various departments were included in the study and either ICU participants were excluded 36 , 37 , or data for non-ICU participants were separately reported 38 , 39 . Two studies included multiple departments and did not report exclusion of ICU participants 13 , 40 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A number of studies were performed at specific non-ICU hospital departments, such as the internal medicine department 32 , general ward 33 , infectious disease ward 34 , or a pulmonary medicine ward 35 (Table 2 ). In other studies, various departments were included in the study and either ICU participants were excluded 36 , 37 , or data for non-ICU participants were separately reported 38 , 39 . Two studies included multiple departments and did not report exclusion of ICU participants 13 , 40 .…”
Section: Resultsmentioning
confidence: 99%
“…In all but one, de-implementation strategies contained an educational component (meetings and/or materials), which was combined with implementation of a clinical practice guideline in five studies [33][34][35][36][37] , reminders in one study 33 , audit feedback in three studies 33,37,40 , an organizational culture intervention in three studies 32,33,35 , and an inter-professional education in one study 39 . The one study without an educational intervention combined implementation of a clinical practice guideline with an organizational intervention 13 .…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Owing to their high efficacy and relative safety, an excess of drug prescriptions has been widespread in Chinese hospitals. [6] However, recent studies have shown that PPIs are associated with an increased risk of some adverse reactions including osteoporotic-related fractures, C difficile infection, community-acquired pneumonia, Vitamin B 12 deficiency, and so on. [7] This case emphasizes the necessity to improve the appropriate and rational use of PPIs for pharmacists.…”
Section: Introductionmentioning
confidence: 99%